2020
DOI: 10.3390/cryst10100890
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation on Dynamic Response of RC T-Beams Strengthened with CFRP under Impact Loading

Abstract: To precisely evaluate the retrofitting effectiveness of Carbon Fiber Reinforced Plastic (CFRP) sheets on the impact response of reinforced concrete (RC) T-beams, a non-linear finite element model was developed to simulate the structural response of T-beams with CFRP under impact loads. The numerical model was firstly verified by comparing the numerical simulation results with the experimental data, i.e., impact force, reaction force, and mid-span displacement. The strengthening effect of CFRP was analyzed from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Shell elements (S4R) were used for the simulation of the CFRP. The mechanical parameters of CFRP developed in this study are given in Table 2 [8,15,16]. Embedded region coupling was employed to describe the connection between longitudinal and transverse reinforcements in concrete.…”
Section: Numerical Modelingmentioning
confidence: 99%
“…Shell elements (S4R) were used for the simulation of the CFRP. The mechanical parameters of CFRP developed in this study are given in Table 2 [8,15,16]. Embedded region coupling was employed to describe the connection between longitudinal and transverse reinforcements in concrete.…”
Section: Numerical Modelingmentioning
confidence: 99%
“…Several manufacturing processes have been studied, such as the effect of laser fabrication [4] and ultrathin electrospun nanofibers on multifunctional fiber-reinforced polymer composites [5]. Various applications of CFRP materials, including in the production of concrete columns [6], Tshaped beams [7], and Belleville springs [8] have been studied. Case studies have revealed the advantage of the reinforced composite structure in diverse industrial applications and the structure is expected to contribute to an emerging market for CFRP materials.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the existence of a reasonable pore structure. Zhao et al [5] used the finite element method for modeling the fundamental behavior of T-beams with carbon fiber-reinforced plastic under impact loads. The results show that the overall stiffness of the T-beams was significantly improved due to the carbon fiber-reinforced plastic strips.…”
mentioning
confidence: 99%